"Xi’nan Opera Exhibition" Provides Contemporary Inspiration to Opera Practitioners - Zhu, Tingting (Journal of Social Science and Humanities, 2024)
As an important milestone in the development of Chinese drama, Xi'nan Opera Exhibition has important implications for the creative work of contemporary opera workers. By analyzing the characteristics of Xi'nan Opera Exhibition in the development of drama, Xi'nan Opera Exhibition, with its eclectic and diversified development attitude, wide selection of repertoires and theatrical sentiment of using foreign things for Chinese purposes, encourages the public to focus on solving contemporary problems, and brings important implications for the social responsibility of contemporary opera creation and the realization of its social functions.